A review of COVID-19 related research in accounting - Iman Harymawan; Nadia Klarita Rahayu (Cogent Business & Management, 2022)
The purpose of this paper is to review COVID-19 and Accounting research published during the pandemic up to February 2021. This study is a literature review that focuses on articles related to COVID-19 and accounting. This study uses articles sourced from the Scopus database. This study discusses COVID-19 in relation to the financial market, corporate social responsibility, firm performance, financial crisis, risk, and corporate governance. The results of this study are expected to help determine future research related to COVID-19 in the accounting field.
Keywords: G34; M14; M40; 650; COVID-19; governance; review